The beginnings of a societal discussion about conscious motherhood on the Polish territories at the turn of the 20th century - Dormus, Katarzyna (Zakład Historii Edukacji Instytutu Pedagogiki Uniwersytetu Wrocławskiego, 2015)
Creating the best possible conditions for bringing up the young has been a topic long debated by educators and politicians. The turn of the 20th century, however, was a time when the debate intensified and took on a new meaning. The discussion had social, economic, health, feminist, and patriotic aspects. Toward the end of the 19th century, the whole of Europe – including the Polish territories – saw a decline in the health as well as the psychological and moral condition of young generations. This was a cause for concern among European societies. A fear of degeneration was fueled by the growing scientific research on heredity. All this was happening amidst changes related to the role of family as a building block of both the state and the nation.
Keywords: conscious motherhood; education; hygiene; national and international legislation on human organs transplantation; ethics